The Alphavirus Sindbis Infects Enteroendocrine Cells in the Midgut of Aedes aegypti - Yani P. Ahearn; Jason J. Saredy; Doria F. Bowers (Viruses, 2020)
Transit of the arthropod-borne-virus (arbovirus) Sindbis (SINV) throughout adult female mosquitoes initiates with its attachment to the gut lumen, entry and amplification in midgut cells, followed by dissemination into the hemolymph. Free-mated adult females, aged day 5–7, were proffered a viremic blood suspension via sausage casings containing SINV-TaV-Green Fluorescent Protein (GFP) at a final titer of 106 PFU/mL. Midguts (MGs) from fully engorged mosquitoes were resected on days 5 and 7 post-bloodmeal, and immunolabeled using FMRFamide antibody against enteroendocrine cells (ECs) with a TX-Red secondary antibody. Following immunolabeling, the organs were investigated via laser confocal microscopy to identify the distribution of GFP and TX-Red. Infection using this reporter virus was observed as multiple GFP expression foci along the posterior midgut (PMG) epithelium and ECs were observed as TX-Red labeled cells scattered along the entire length of the MG. Our results demonstrated that SINVGFP did infect ECs, as indicated by the overlapping GFP and TX-Red channels shown as yellow in merged images. We propose that ECs may be involved in the SINV infection pathway in the mosquito MG. Due to the unique role that ECs have in the exocytosis of secretory granules from the MG and the apical-basolateral position of ECs in the PMG monolayer, we speculate that these cells may assist as a mechanism for arboviruses to cross the gut barriers. These findings suggest that MG ECs are involved in arbovirus infection of the invertebrate host.